Broadband Reflective Optical Limiter Using GST Phase Change Material - Andrew Sarangan; Josh Duran; Vladimir Vasilyev; Nicholaos Limberopoulos; Ilya Vitebskiy; Igor Anisimov (IEEE Photonics Journal)
We experimentally demonstrate a thermally induced reflective optical limiter using Ge $_2$ Sb $_2$ Te $_5$ (GST) and SiO $_2$ in a multilayer photonic bandgap edge-filter configuration. In the PASS state, greater than 80% transmission was achieved at $λ \sim 1500$ nm over a 300 nm spectral bandwidth and $± 45^{° }$ angles of incidence. In the BLOCK state, extinction ratios higher than 30 dB were achieved. By comparison, all previous optical limiters based on nonlinear photonic crystals have severe spectral bandwidth and/or angle of incidence limitations in either the PASS or BLOCK states. A nine-layer implementation of this device was fabricated and tested in this paper. Numerical modeling results show reasonable agreement with measured values. To the best of our knowledge, this is the first demonstration of optical limiting over a broad spectral band using phase change materials with this level of performance. However, it should be noted that although GST can be switched in both directions, the experimental results demonstrated in this paper are limited to PASS-to-BLOCK switching only.